Rebamipide, an Amino Acid Analog of 2(1H)-Quinolinone, Inhibits the Formation of Human Osteoclasts. (14th November 2016) - Nanke, Yuki; Kobashigawa, Tsuyoshi; Yago, Toru; Kawamoto, Manabu; Yamanaka, Hisashi; Kotake, Shigeru
Abstract : Objectives . Drug repositioning or drug reprofiling (DR) has recently been growing in importance. DR has a significant advantage over traditional drug development because the repositioned drug has already passed toxicity tests; its safety is known, and the risk of adverse toxicology is reduced. In the current study, we investigated the role of rebamipide, a mucosa-protecting agent, with recently reported anti-inflammatory function, in human osteoclastogenesis. Methods. Peripheral blood mononuclear cells (PBMCs) were cultured in the presence of M-CSF and sRANKL. Osteoclast formation was evaluated by immunohistological staining for CD51/61 (vitronectin receptors). Osteoclast formation, in the presence or absence of rebamipide (0, 1, and 3 mM), was observed by time-lapse photography and actin ring formation. The number of absorption sites and area of absorption were calculated using Osteologic™ plates. Pit formation was studied by 3D-SEM. Results . Rebamipide inhibited human osteoclast formation at 3 mM, a pharmacological concentration, and inhibited resorbing activity dose-dependently. Rebamipide induced the degradation of actin rings in mature osteoclasts. This mechanism may involve inhibiting the osteoclast fusion pathway through reducing the expression of DC-specific transmembrane protein (DC-STAMP). Conclusions . The present study suggests that rebamipide would be useful as a novel agent for osteoporosis and rheumatoid arthritis.